Réponses

  • Utilisateur Brainly
2014-03-21T18:20:19+01:00
factoriser les expressions suivantes: 

3x-15= 3(x-5)

 -2x+8=2(4-x)   

4x²-2x=(2x)(2x-1)

21y-14z+7b=  7(3y-2z+b)

3a-3= 3(a-1)

20x²-15x+5= 5(4x²-3x+1)                

 12y³-8y²+16y=
(4y)(3y²-2y+4)
2014-03-21T18:38:15+01:00
Factoriser les expressions suivantes :

3x - 15 = 3 (x - 5)

-2x + 8 = 2 (4 - x)   

4x² - 2x = (2x) (2x - 1)

21y - 14z + 7b = 7 (3y - 2z + b)

3a - 3 = 3 (a - 1)

20x² - 15x + 5 = 5 (4x² - 3x + 1)                

12y³ - 8y² + 16y = 
(4y) (3y + 3y - 2y + 4)